Current issues in immunisation (Moving the second dose of measles-mumps-rubella vaccine to school entry: implications for control of rubella) - Heath, Timothy C; Burgess, Margaret A; Forrest, Jill M (Communicable Diseases Intelligence, 1998)
This article discusses the implications for the control of rubella resulting from changing the immunisation schedule for the second dose of the measles-mumps-rubella vaccine.